ANALISIS RASIONALITAS TERAPI PADA PASIEN TUKAK PEPTIK DI INSTALASI RAWAT INAP RS X KOTA SAMARINDA - Irham Bakhtiar, Muh.; Mukti, Chera Ananda (JIFI (Jurnal Ilmiah Farmasi Imelda), 2023)
Peptic ulcer is one of the most common gastrointestinal diseases and affects almost 10% of the world's population. Ideally peptic ulcer treatment should be highly effective, free of significant side effects, easy to comply with, and cost effective. This study aims to determine the treatment profile of peptic ulcer patients at the inpatient installation of RS X Kota Samarinda and to determine the rationality of treatment for ulcer patients at the inpatient installation of RS X Kota Samarinda. The research was conducted using a retrospective method. Data collection in this study used a purposive sampling technique in accordance with the inclusion and exclusion criteria and obtained 37 samples of medical record data. Based on the results of the study, it was found that the results of the treatment profile in peptic ulcer patients, the most widely used type of therapy was a combination of PPI (proton pump inhibitor) + cytoprotective (mucosal protector) of 54.1% and a combination of PPI (proton pump inhibitor) + antibiotics + cytoprotective of 54.1%. 10.8%. The most widely used drugs were omeprazole (37.9%), sucralfate (27.5%), lansoprazole (6.9%), amoxicillin (6.9%), clarithromycin (6.7%), pantoprazole (5, 7%), ranitidine (5.6%), rebamipide (2.2%), and metronidazole (1.1%). Rationality in peptic ulcer patients on the use of antibiotics with the Gyssens method obtained category 0 in 5 patients (83.3%) and category IVA in 1 patient (16.7%). Rationality in peptic ulcer patients on the use of gastric acid controlling drugs was found to be 97.3% correct indication, 62.2% correct dose, 100% correct duration.